Readiness for self-directed learning among nursing students in a medical college, Chitwan - Singh, Indu; Paudel, Binita (Journal of Chitwan Medical College, 2020)
Background: Self-directed learning is a type of instructional strategy where students take charge of their learning process. Self-directed learning is learning approach where learners are responsible towards learning which helps students think critically and perform task confidently. The skills that are learned through self-directed learning remain lifelong and helps to provide patient care in effective way and uplifting the nursing profession. This study was conducted to identify the readiness for self-directed learning among nursing students in Chitwan Medical College. Methods: A descriptive cross-sectional study design was adopted. Sample size was 107 nursing students from Bachelor in science of nursing and Bachelor in nursing science program. They were selected by using probability, stratified, simple random technique. A standardized tool (Self Directed Learning Readiness Scale) was used to collect data. Data were analyzed by using descriptive statistics and inferential statistics. Results: More than two-third of the nursing students were ready for self-directed learning. The mean score of self control was higher than the mean score of self-management and mean score of desire. The level of the readiness for self-directed learning was significantly associated with age (p=0.036), ethnicity (0.036) and most prefer resource (p=0.010). Conclusions: Self-directed learning helps for self control towards their learning and enable students move forward towards their career goal. So, the faculties need to focus on the selection resources for learning that help to create desire for learning and promote self-directed learning skills among nursing students.